Analysis on Construction Cost Estimation Ministry Regulation Year 2016 and Year 2022 for Construction Projects - Putra, Andi Bayu; Setyandito, Oki (Fakultas Sains dan Teknologi Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
Cost is one of the 3 most important project management components, with the other two being Quality and Time. The calculation of construction work costs in detail is regulated in Indonesia by a Ministry Regulation. This Ministry Regulation has only undergone changes in 2022, which replaces and/or fixes several existing rules in the previous Regulation issued in 2016. For brevity, the two Regulations is shortened to regulation 2016 and regulation 2022. Of course, the accuracy of these regulations is especially important regarding the smooth implementation of projects. This study uses the two Ministry Regulations on two different Construction Projects to see analyse the different result of cost calculation caused by the regulation change. This change itself is important to be understood to continuously improve the Ministry Regulation regarding cost estimation. In conclusion, regulation 2022 can produce a more accurate results, with regulation 2016 often gives a higher cost estimation than regulation 2022. For future research it is best to analyse other type of construction infrastructure to gain more insight into which estimation that can still be improved in the future.